Monitoring of Noctiluca Bloom in Mandapam and Keelakarai Coastal Waters; Southeast Coast of India - Arumugam, R.R.R. Kannan,A. Hemalatha,A. Kannathasan,P. Sampathkumar,T. Balasubramanian, P. Anantharaman*,G. Thirumaran, R. (Recent Research in Science and Technology, 2010)
Monitoring the Harmful Algal Blooms was carried out during July to December 2008 in Mandapam and Keelakarai coastal waters of Tamil Nadu, Southeast coast of India. In the month of October several fishes and shellfishes were died due to Noctiluca blooms along these two areas. The present investigation the following species of phyto and zooplankton were found to be common; phytoplankton such as Coscinodiscus sp., Skeletonema costatum, Bacillaria paradoxa, Thallassiothrix frauenfeldii, T. longisima, Leptocylindrus sp., and zooplankton such as Paracalanus parvus, Acrocalanus gracilis, Pseudodiaptomus serricautatus, Rhincalanus cornutus, R. nasutus, Euterpina acutifrons, Nannocalanus minor, Eucalanus attenuates, E. crassus, Fish larvae, Fish eggs, Barnacle nauplii, Bivalve larvae, Gastropod larvae, Copepod nauplii and Mysis larvae. The hydrobiological parameters also analysed during bloom and after blooms; the dissolved oxygen (2.6 – 4.9µM L-1) nutrients varied between nitrate (0.66 – 1.01µM L-1) nitrite (0.11 – 0.21µM L-1) phosphate (0.51 – 0.86µM L-1) and silicate (0.81 – 4.2µM L-1).